Arquitectura orientada a servicios web para el desarrollo de instituciones de educación superior en Colombia - Pérez Castillo, José Nelson; Castro Vargas, Blanca Magdalena (Ingeniería, 2008)
Three great challenges faced by Colombian Higher Education in the present millennium are: pertinence, quality and internationalization. Undoubtedly, these three requirements have a fundamental support on modern Information Technologies, Communications and Knowledge Management (TICs & GC). In the document herein, we show architecture with several logic levels fully oriented to Web services, where it is possible to carry out modernization processes within Colombian Higher Education Institutions, for assuming the stated challenges, through the intensive use of the above mentioned technologies.